Associations of low-carbohydrate diets patterns with the risk of hyperuricemia: a national representative cross-sectional study in Korea - Seungyoun Jung; Yoon Jung Park (Nutrition Journal)
Abstract Background The association between low-carbohydrate diets and hyperuricemia risk, a significant risk factor for gout and cardiometabolic morbidities, remains inconclusive, partly due to differing effects of replacing carbohydrates with animal- or plant-based macronutrients. This study examined associations between low-carbohydrate diet patterns and hyperuricemia risk in 39,880 adults in the Korea National Health and Nutritional Examination Study 2016–2022. Methods Diet was assessed via a 24-hour dietary recall. The overall, animal-rich, and plant-rich low-carbohydrate diet score (LCDS) was calculated based on percent energy derived from protein and fat in animal and plant food sources. Hyperuricemia was defined as serum uric acid levels > 7.0 mg/dL for men and > 6.0 mg/dL for women. Multivariate-adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using logistic regression models to estimate the risk of hyperuricemia across quintiles of LCDS. Results A significantly greater risk of hyperuricemia was observed among individuals with higher overall LCDS (OR for quintile 5 vs. quintile 1 [Q5vs.Q1]: 1.41, 95%CI:1.22–1.63, P-trend: <0.001) and animal-rich LCDS (ORQ5vs.Q1: 1.28, 95%CI:1.12–1.47, P-trend: <0.001), but not with plant-rich LCDS (ORQ5vs.Q1: 1.00, 95%CI: 0.87–1.16). These positive associations for overall LCDS and animal-rich LCDS were evident in overweight individuals (ORQ5vsQ1: 1.53, 95%CI: 1.29–1.82 for overall LCDS; and 1.39, 95%CI: 1.19–1.63 for animal-rich LCDS; all P-trends < 0.001), but not in non-overweight individuals (all P-interactions: <0.001). Conclusions In our study, animal-based low-carbohydrate diets were associated with a greater risk of hyperuricemia, while no association was observed for plant-based low-carbohydrate diets. Larger cohort studies are warranted to replicate these findings.